The Effect of Healing Touch and Dhikr Therapy on Reducing Blood Pressure in Hypertensive Patients at The Jati Health Center - Nabilla, Amanda Putri; Sukarmin; Suwarto, Tri (International Journal of Health and Pharmaceutical (IJHP), 2026)
Hypertension is one of the chronic health problems that is at risk of causing cardiovascular complications if not managed optimally. In addition to pharmacological therapy, a nonpharmacological approach is needed as a complementary therapy to help lower blood pressure. This study aims to determine the effect of healing touch and dhikr therapy on reducing blood pressure in hypertensive patients. This study used a quasi-experimental design with a pretest-posttest design with a control group. The number of respondents was 46 hypertensive patients who were divided into intervention groups and control groups. The intervention group was given a combination of healing touch and dhikr therapy, while the control group only received standard therapy. Analysis of blood pressure differences before and after intervention in the intervention group was conducted using the Wilcoxon test for systolic blood pressure and the paired t-test for diastolic blood pressure. In the control group, the analysis was carried out using the Wilcoxon test. The comparison of blood pressure drops between groups was analyzed using the Mann–Whitney test. The results showed that systolic and diastolic blood pressure in the intervention group experienced a statistically significant decrease (p < 0.001). The decrease in blood pressure in the intervention group was greater than in the control group, and the difference was statistically significant (p < 0.001). It can be concluded that the combination of healing touch therapy and dhikr is effective as a complementary therapy in lowering blood pressure in hypertensive patients.